METODE KLASIK DALAM PENGAMBANGAN WEB SISTEM INFORMASI KOMUNITAS MARVEL INDONESIA - Ani Rachmaniar; Susi Widayati; Kokoy Rokoyah (Journal of Information System, Informatics and Computing, 2026)
Hobby-based communities play a crucial role in connecting individuals with shared interests, including the Marvel fan community in Indonesia, which encompasses comics, feature films, and even action figure collections. However, limited access to official information about community activities hinders the public from learning more about its existence and activities. Therefore, a structured and easily accessible information medium is needed. The system development method in this research was conducted through data collection using literature studies and internet sources related to the activities of the Indonesian Marvel Community. Next, a web-based information system was designed and built using PHP as the backend programming language and MySQL as the database. This system was developed to present integrated information, including a community profile, a brief history, a schedule of upcoming activities, documentation of past activities, and visitor reviews. The results of the study indicate that the developed information system is able to meet the need for providing official information regarding community activities in a more effective and structured manner. Furthermore, this system also demonstrates that the Indonesian Marvel Community has a broad reach, not only centered in the capital but also spread across various major cities in Indonesia. The presence of this system is expected to increase community participation and have a positive impact on individuals with similar interests through the provision of accurate and easily accessible information.